Analisis Perbedaan Struktur Ekonomi Kota Balikpapan dan Kota Bontang - Teguh Hadi Wijaya; Muhammad Saleh; Emilya Umma Aziza Gaffar (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to analyze the economic sector basis, a shift in the economic sector and the comparison of the economic structure in the city of Balikpapan and Bontang. In this study, using an analysis tool Location Quotient, Shift Share, Index Divergence Krugman and T test of two independent variables, but it is also aided by a computer system that uses Microsoft Office Excel 2010 and SPSS version 22. Unknown sector of a base in the city of Balikpapan is the manufacturing, electricity, gas and water supply, construction, trade, hotels and restaurants, transport and communications and services. Bontang sector basis is the manufacturing and building. Known from shift share analysis and index divergences Krugman that the economic structure of Balikpapan and Bontang is the same it can be seen from the same sector that is dominant in the secondary sector. These results are consistent with the results of T test to the results of two independent variables t t table.Keywords:    Sector Economy, Locationt Quotient, Shift share and index Divergence Krugman